1985
DOI: 10.1152/jappl.1985.58.5.1676
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral factors influencing expression of pressor reflex evoked by muscular contraction

Abstract: The effect of evoked muscle tension, active muscle mass, and fiber-type composition on the pressor reflex evoked by muscular contraction was examined in decerebrate and anesthetized cats. Muscular contraction was induced by stimulating the L7 and S1 ventral roots with 0.1-ms duration pulses three times motor threshold at various frequencies. The experiments were designed to isolate the variable under study as much as possible and included the use of selectively denervated preparations to limit contractions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 0 publications
2
33
1
Order By: Relevance
“…Although the difference in findings between the present report and the study of Stebbins et al (37) may be due to species effects, it should be noted that the relative mass (i.e., as a percentage of total body muscle mass) of the triceps surae muscle in the cat is much larger than the relative mass of the wrist muscles and fingers flexors of the human. Previous work (19) suggests that the muscle mass is linked to the magnitude of the pressor response. Although stretch of forelimb cat muscles evoked significantly greater cardiovascular responses than those noted during hindlimb muscle stretch (12), it is unknown whether stretch of very small muscle mass in the cat could evoke significant autonomic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the difference in findings between the present report and the study of Stebbins et al (37) may be due to species effects, it should be noted that the relative mass (i.e., as a percentage of total body muscle mass) of the triceps surae muscle in the cat is much larger than the relative mass of the wrist muscles and fingers flexors of the human. Previous work (19) suggests that the muscle mass is linked to the magnitude of the pressor response. Although stretch of forelimb cat muscles evoked significantly greater cardiovascular responses than those noted during hindlimb muscle stretch (12), it is unknown whether stretch of very small muscle mass in the cat could evoke significant autonomic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, Some pathophysiological conditions are associated with alterations in group III/IV afferent sensitivity or their elicited reflexes (Murphy et al, 2011). In addition, the role of these fibers can vary across skeletal muscle fiber type and muscle group (Iwamoto and Botterman, 1985, Martin et al, 2006), and thus the picture is not actually so simple. Indeed, the increase in afferent feedback achieved by the increase in active muscle mass in our study from KE to BIKE was likely not directly proportional to the change in muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between the magnitude of afferent feedback and muscle mass has long been established (Freund et al, 1978, Iwamoto and Botterman, 1985). Freund et al (Freund et al, 1978) demonstrated that post-bicycle exercise occlusion of blood flow to both legs maintained mean arterial pressure at a higher level than occlusion of one leg alone.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been suggested that muscles composed of slow twitch fibers do not generate a pressor response when stimulated to contract (26). However, this issue remains unsettled since others have shown in a cat model that the slow twitch soleus muscle will generate a pressor response if made to contract maximally (27).…”
Section: Experimental Protocolsmentioning
confidence: 99%